Development of an Evaluation Framework Suitable for Assessing Humanitarian Workforce Competencies During Crisis Simulation Exercises. Issue 1 (15th January 2014) - Cranmer, Hilarie; Chan, Jennifer L.; Kayden, Stephanie; Musani, Altaf; Gasquet, Philippe E.; Walker, Peter; Burkle, Frederick M.; Johnson, Kirsten
Abstract The need to provide a professionalization process for the humanitarian workforce is well established. Current competency-based curricula provided by existing academically affiliated training centers in North America, the United Kingdom, and the European Union provide a route toward certification. Simulation exercises followed by timely evaluation is one way to mimic the field deployment process, test knowledge of core competences, and ensure that a competent workforce can manage the inevitable emergencies and crises they will face. Through a 2011 field-based exercise that simulated a humanitarian crisis, delivered under the auspices of the World Health Organization (WHO), a competency-based framework and evaluation tool is demonstrated as a model for future training and evaluation of humanitarian providers. <mixed-citation id="ref" publication-type="journal"> <string-name> <given-names>H</given-names> <x content-type="archive" xml:space="preserve"> </x> <surname>Cranmer</surname> </string-name>, <string-name><given-names>J</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Chan</surname></string-name>, <string-name><given-names>S</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Kayden</surname></string-name>, <string-name><given-names>A</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Musani</surname></string-name>, <string-name><given-names>P</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Gasquet</surname></string-name>, <string-name><given-names>P</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Walker</surname></string-name>, <string-name><given-names>F</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Burkle</surname></string-name>, <string-name><given-names>K</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Johnson</surname></string-name>. Development of an evaluation framework suitable for assessing humanitarian workforce competencies during crisis simulation exercises . <source>Prehosp Disaster Med</source>. <year>2014</year>;<volume>29</volume>(<issue>1</issue>):<fpage>1</fpage>-<lpage>6</lpage></mixed-citation>.